PELATIHAN PENGENALAN WARNA UNTUK BERBAGAI MEDIA PEMBELAJARAN SENI RUPA DAN DESAIN GRAFIS DI DESA BAUNG SENGATAP KABUPATEN SINTANG KALIMANTAN BARAT - Rusdi, Rusdi; Warkintin, Warkintin; Arroi, Yakobus; Ayu, Revira (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2025)
In this Community Service (PkM) activity, we aim to provide insight into color to be used as a learning medium for fine arts and graphic design. The target of PkM is aimed at people who enjoy fine arts, teachers, students and students in various schools. This PkM activity also aims to foster the creativity of teenagers and lovers of the world of fine arts and graphic design, in addition to maintaining the values of fine arts in society so that they can be more creative in accordance with the culture in Baung Sengatap village. After PkM is carried out, it is hoped that it will produce new works and products that are better and more balanced with the results of the color combinations that have been studied. In its implementation, we start with planning the concept of primary colors. Next is an introduction to the concept of secondary colors. After that, an introduction to tertiary colors. After the introduction is given to the participants, the next step is direct practice on mixing primary colors. After the primary colors are understood by the PkM participants, the next step is an introduction to direct practice on mixing secondary colors, and when the primary and secondary colors are understood, directions will be given for direct practice with tertiary colors.Keywords: Color, Learning Media, Graphic Design Fine Arts.Rasakan sensasi serunya bermain tanpa hambatan di situs link gacorqq, kesempatan mendapatkan jackpotnya cukup mudah dan sangat cepat.